Zróżnicowanie roślinności leśnej Nadleśnictwa Herby - Domagała, Paweł; Bodziarczyk, Jan; Różański, Wojciech (Leśne Prace Badawcze, 2022)
The phytosociology of the forests in the Herby Forest District has not been thoroughly examined so far with the exception of a few studies that concentrated on small parts of afforested areas. One of the main aims of this study was to comprehensively characterize all forest communities in the Herby Forest District. Our methods for data collection were based on the Central European phytosociological approach of the Braun-Blanquet school. Data from over 300 relevés were gathered in the field and then classified using numerical methods resulting in 17 vegetation units, including 11 forest communities and lower syntaxons. Querco roboris-Pinetum and Leucobryo-Pinetum were the dominating forest communities in the Herby Forest District. This result is generally in accordance with previous findings from the forest vegetation analyses conducted by other authors in this area. However, the presence of some forest communities described in previously published studies was not confirmed; instead several new communities were identified. These new communities are mostly the result of forest management. Furthermore, based on our results we were able to derive new information about the distribution, differentiation, developmental stage and degree of preservation of some forest communities.